Automating Test Case Generation for Android Applications using Model-based Testing - Khan, Usman Habib; Khan, Muhammad Naeem Ahmed; Mirza, Aamir Mehmood; MUHAMMAD AKRAM; Shariqa Fakhar; Shumaila Hussain; Magsi, Irfan Ahmed; Wagan, Raja Asif (EMITTER International Journal of Engineering Technology, 2022)
Testing of mobile applications (apps) has its quirks as numerous events are required to be tested. Mobile apps testing, being an evolving domain, carries certain challenges that should be accounted for in the overall testing process. Since smartphone apps are moderate in size so we consider that model-based testing (MBT) using state machines and statecharts could be a promising option for ensuring maximum coverage and completeness of test cases. Using model-based testing approach, we can automate the tedious phase of test case generation, which not only saves time of the overall testing process but also minimizes defects and ensures maximum test case coverage and completeness. In this paper, we explore and model the most critical modules of the mobile app for generating test cases to ascertain the efficiency and impact of using model-based testing. Test cases for the targeted model of the application under test were generated on a real device. The experimental results indicate that our framework reduced the time required to execute all the generated test cases by 50%. Experimental setup and results are reported herein.